Meridional Asymmetry in Recent Decadal Sea‐Level Trends in the Subtropical Pacific Ocean - F. Schloesser; P. R. Thompson; C. G. Piecuch (Geophysical Research Letters)
Abstract Recent sea surface height (SSH) trends in the South Pacific are substantially greater than trends in the North Pacific. Here, we use the Estimating the Climate and Circulation of the Ocean Version 4 Release 4 ocean state estimate and the Ocean Reanalysis System 5 to identify the forcing and mechanisms underlying that meridional asymmetry during 2005–2015. Thermosteric contributions dominate the spatial structure in Pacific SSH trends, but contributions from local surface heat fluxes are small. Wind stress trends drive a spin‐up of the South Pacific subtropical gyre and a northward shift of the North Pacific subtropical gyre. A reduced gravity model forced with reanalysis winds qualitatively reproduces the meridional seesaw in sea level, suggesting that asymmetric trends in subtropical wind stress drive a cross‐equatorial heat transport. A reversal in forcing associated with this process could impact near‐term rates of coastal sea‐level change, particularly in Pacific Island communities.